The use of equine influenza pseudotypes for serological screening - Scott, Simon (Library Publishing Media, 2012)
Standard assays used for influenza serology present certain practical issues, such as inter-laboratory variability, complex protocols and the necessity for handling certain virus strains in high biological containment facilities. In an attempt to address this, avian and human influenza HA pseudotyped retroviruses have been successfully employed in antibody neutralization assays. In this study we generated an equine influenza pseudotyped lentivirus for serological screening. This was achieved by co-transfection of HEK293T cells with plasmids expressing the haemagglutinin (HA) protein of an H3N8 subtype equine influenza virus strain, HIV gag-pol and firefly luciferase reporter genes and harvesting virus from supernatant. In order to produce infective pseudotype particles it was necessary to additionally co-transfect a plasmid encoding the TMPRSS2 endoprotease to cleave the HA. High titre pseudotype virus (PV) was then used in PV antibody neutralization assays (PVNAs) to successfully distinguish between vaccinated and non-vaccinated equines. The sera were also screened by single radial haemolysis (SRH) assay. There was a 65% correlation between the results of the two assays, with the PVNA assay appearing slightly more sensitive. Future work will extend the testing of the PVNA with a larger number of serum samples to assess sensitivity/specificity, inter/intra-laboratory variability and to define a protective titre.